Pigmented Ethnic Skin and Imported Dermatoses A Text-Atlas (Springer International Publishing, 2018)
The vast majority of the global population has pigmented non-Caucasian skin; accordingly, this book focuses on the diagnosis and management of skin diseases in dark-skinned populations, paying particular attention to different reactive profiles, the frequency and the clinical pictures of diseases in pigmented ethnic skin that arise in hot climate zones. Supplemented by a wealth of high-quality, full-color images, this comprehensive work covers the full range of dermatological entities and issues characteristic of the tropical and subtropical regions of the globe, including those that are now emerging in developed countries as a result of intensified travel, globalized business, and migration. Each disorder is described by respected experts on subtropical and tropical countries, and each chapter is clearly structured, examining the incidence, pathogenesis, clinical presentation, management and course. The book illustrates the clinical features and includes major schedules for the diagnosis and management of skin diseases presented in darkly pigmented to black skin. As such, it offers an invaluable tool for all dermatologists in developing and developed countries, especially those who are used to dealing with skin lesions mainly in white Caucasian skin. While enabling physicians to provide proper advice, medical services and support, Pigmented Ethnic Skin and Imported Dermatoses also represents a guide for a broader range of professionals working for governmental institutions, health and refugee agencies.